Ingresos tributarios provenientes del sector minero y su relación con la recuperación económica del Perú - Coaquira Taboada, Jhennie Neysha (2022)
Objective: To estimate a relation between the collection of tax revenues with those from the mining sector, with consideration of the economic recovery of the post-pandemic context in Peru. Method: The research approach was descriptive and correlational level under the Pearson method, oriented to the tax collection of the mining sector and the revenues collected in Peru between 2012 and 2021; in addition, a non-experimental and cross-sectional design was used with information obtained from official sources of the National Superintendence of Customs and Tax Administration (SUNAT). Results: There is a moderate positive correlation between the collection of tax revenues from the mining sector and total tax revenues. The relationship is presented with the participation of the mining sector, which comprises a large percentage of such revenues. Conclusion: There is a positive correlation between the collection of tax revenues from the mining sector and the economy’s recovery, since it settles the country's income for its operations and recovery after the pandemic, maintaining itself as a stable sector. Also, giving that it is a sector that has an incidence degree in tax collection, it becomes essential to strengthen it to boost the national economy.